Surgical Outcomes of Combined Phacoemulsification and Silicone oil Removal in Post Retinal Detachment Surgery Patients: Doi:10.36351/pjo.v36i4.1116 - Haseeb, Uzma; Haseeb, Muhammad; Rehman, Aziz ur (Pakistan Journal of Ophthalmology, 2020)
Purpose: To evaluate the surgical outcomes of Combined Phacoemulsification with IOL implantation and Silicone oil removal in patients with previous retinal surgery. Study Design: Interventional case series. Place and Duration of Study: Al-Ibrahim eye Hospital Karachi from January 2019 to December 2019. Methods: Total 30 eyes of 30 patients between ages of 25 to 65 years, who had retinal detachment surgery with silicone oil used as internal tamponade and later on developed cataract were re-operated once confirming that retinal was attached. The time interval between two surgeries was 8 to 10 months. Phacoemulsification with IOL implantationwas done followed by silicone oil removal by 23-gauge pars plana method. Postoperative follow-ups were done at day 1, 1 month and at 6 months to record visual acuity and retinal status. Results: Best corrected Visual acuity was recorded pre and post-operatively using Snellen chart. Preoperatively 12 patients had visual acuity of 6/60, 12 with vision 6/95 and 6 with 6/120. There was improvement of 2 lines of visual acuity post operatively as recorded by Snellen chart. Retina was attached in 28 (93.33%) patients and 2 (6.66%) had re-detached retina at the end of 6 months. Conclusion: Visual outcomes were found to be better with low rate of retinal re-detachment after 6 months follow-up of combined phacoemulsification with IOL implantation and silicone oil removal. Hence, Combined Phacoemulsification with Silicone oil removal is a method that is associated with better visual and anatomical outcomes as well as decrease the chances of patients undergoing third surgery for cataract extraction. Key Words: Retinal Detachment, Phacoemulsification, Silicon Oil.